Determinants of Career Choice between Entrepreneurship and Employment: A PLS-SEM Approach - Mahdi, Irfan (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the determinants of career choice between entrepreneurship and employment by examining the role of interest, motivation, social influence, and family factors. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) based on data collected from 251 respondents. The results indicate that motivation (β = 0.343) and interest (β = 0.210) have significant positive effects on entrepreneurial career choice, while social influence (β = 0.029) and family influence (β = 0.125) show relatively weak effects. In contrast, all independent variables exhibit very low effects on employment career choice, suggesting limited explanatory power of the model for this outcome. The model explains 38.7% of the variance in entrepreneurial career choice and 40.5% in employment career choice, indicating moderate explanatory power. These findings suggest that entrepreneurial career decisions are primarily driven by internal psychological factors, whereas employment decisions are likely influenced by external conditions beyond the variables examined in this study. This study contributes to the literature by integrating economic and psychological perspectives in explaining dual career choices within a unified PLS-SEM framework.